A mesoscale solidification simulation of fusion welding in aluminum-magnesium-silicon alloys - Rajani, H.R. Zareie; Phillion, A.B. (Elsevier, 2014)
A 3D granular model has been developed to simulate solidification during fusion welding of Al alloys. The model simulates the gradual development of the weld mushy zone composed of both continuous liquid films and solidifying grains by coupling thermal fields based on the Rosenthal equation, a modified Voronoi tessellation to provide grain structure at the meso-scale, and the evolution in fraction solid within a grain based on the Scheil equation. The shape and geometry of the columnar and equiaxed grains within the weld pool has been characterized from experiments and therefore the model can be used to link the solidification behaviour of individual grains to the macroscopic properties of the weld. The gradual formation of micro liquid channels lying along the grain boundaries within the mushy zone is investigated and the role of welding parameters including amperage and welding speed on transitions in the semi solid microstructure is explored. The study reveals that the ability of the micro liquid channels to feed molten metal into the solidifying areas is not uniform through the weld, and is strongly affected by grain size since smaller grains hinder the feeding ability of the mushy zone.
Keywords: Solidification; Welding; Modelling; Microstructure; Meso-scale